A chloride salt freeze-thaw resistant glass fiber reinforced plastic composite material, preparation method and application in preparing water intake head
By grafting nanoparticles and epoxidized polybutadiene on the surface of polyimide fibers, the interface strength between the resin and the glass fiber cloth is enhanced, solving the freeze-thaw resistance problem of epoxy resin fiberglass in salt water environment and achieving long-term stability of the material in harsh natural environments.
Patent Information
- Application Number
- CN202510633618.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-09-16
- Estimated Expiration
- 2045-05-16
AI Technical Summary
Existing epoxy resin fiberglass materials have insufficient resistance to freeze-thaw cycles in saltwater environments, resulting in damage to the chemical bonds at the interface between the resin and the glass fiber cloth, reduced material strength, and difficulty in long-term stable operation in complex natural environments.
Polyimide fibers grafted with nanoparticles on the surface are used to form a complex mechanical interlocking structure with resin and glass fiber cloth to enhance the interface strength. Epoxidized polybutadiene is used to improve the impact toughness to prepare chloride salt freeze-thaw resistant fiberglass reinforced plastic composites.
The material's resistance to freeze-thaw cycles in saltwater environments is improved, maintaining structural integrity and stability, making it suitable for harsh natural water environments.
Smart Images

Figure CN120137354B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of epoxy resin composite materials, and particularly relates to a chloride salt freeze-thaw resistant glass fiber reinforced plastic composite material, a preparation method and application in preparing a water intake head. Background Art
[0002] A water intake head is a common water inlet structure, primarily consisting of a housing, water inlet, filter, grit chamber, outlet, and fixtures. Besides collecting water, performing preliminary filtration, grit settling, and stabilizing water flow, the intake head also provides physical protection for internal components such as the water inlet, filter, and grit chamber, protecting them from water erosion, debris impact, and environmental corrosion. Therefore, the intake head must possess high strength and excellent corrosion resistance to ensure long-term, stable operation in complex natural environments.
[0003] Common water intake heads are made of reinforced concrete or steel. Reinforced concrete water intake heads offer excellent compressive strength, durability, and impermeability, enabling long-term stable operation in complex natural environments and water flow conditions. Steel plate water intake heads, on the other hand, offer advantages such as high strength, relatively light weight, and ease of processing and installation. Therefore, reinforced concrete or steel plate water intake heads are widely used, as exemplified by patent CN212153544U, which discloses a river water intake pontoon for concrete production, and patent CN103556673B, which discloses a multifunctional water intake head for seawater. However, reinforced concrete water intake heads are heavy and difficult to transport and install. While steel water intake heads are lighter, they require high corrosion protection costs in corrosive environments and have shorter maintenance cycles. Fiberglass (FRP) has a much lower density than reinforced concrete and steel, but its strength can match or even exceed that of steel. This means that, while maintaining the same load-bearing capacity, replacing reinforced concrete or steel with FRP for water intake heads can significantly reduce weight, lowering transportation, installation, and support costs.
[0004] Patent CN115216115B discloses a fiberglass wrapped component, its preparation method, and its application, as well as glass fiber cloth and a resin composition. The resin composition comprises the following raw materials: epoxy resin, silane coupling agent, and curing agent; the mass ratio of the epoxy resin to the silane coupling agent is 100:0.3-5. Patent CN105175998B discloses a high-pressure epoxy fiberglass pipe and its preparation method incorporating glass fiber fabric. The high-pressure epoxy fiberglass pipe is made from the following raw materials in parts by weight: 100 parts bisphenol A epoxy resin; 70-85 parts curing agent; 1.5-4 parts accelerator; 0.22-0.60 parts wetting agent; 450-560 parts direct yarn; and 24-60 parts glass fiber fabric. The above is a common epoxy resin-based fiberglass reinforced plastic (FRP) that inherits the lightweight and high-strength characteristics of FRP. Due to its epoxy resin base, it also boasts superior acid and alkali corrosion resistance compared to phenolic resin FRP and unsaturated polyester FRP. However, the complexity of natural water bodies in reality is far beyond imagination. In addition to the common acid-base environment, it is also rich in salt. In such an environment, the water head faces many severe challenges such as high and low temperature, freeze-thaw cycles, etc. Due to the strong rigidity of epoxy resin and the thermal expansion mismatch between epoxy resin and glass fiber cloth, the chloride ion ion radius is small and has strong penetration ability. Under the combined action of chloride salts and repeated freeze-thaw cycles, the permeability of water at the interface is accelerated, the chemical bond between the resin and the glass fiber cloth is destroyed, and the material strength is significantly reduced. Therefore, it is necessary to develop an epoxy resin fiberglass with excellent resistance to freeze-thaw cycles in a saltwater environment, so that it can become an ideal material that can replace reinforced concrete or steel. Summary of the Invention
[0005] To solve the above technical problems, the present invention provides a chloride-salt freeze-thaw-resistant glass fiber reinforced plastic composite material, a preparation method and an application thereof. The glass fiber reinforced plastic composite material includes a polyimide fiber with nanoparticles grafted on the surface through chemical bonds. The grafted nanoparticles have good adsorption properties for chloride ions and can also increase the roughness of the polyimide fiber surface, forming a complex mechanical interlocking structure with the resin and glass fiber cloth, enhancing the physical meshing effect between the resin and glass fiber cloth interface, increasing the interface strength, and improving the chloride-salt freeze-thaw cycle resistance of the composite material.
[0006] In order to achieve the above objectives, the following technical solutions are adopted:
[0007] A chloride salt freeze-thaw resistant glass fiber reinforced plastic composite material comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20-30 parts of curing agent, 400-500 parts of alkali-free glass fiber cloth, 30-40 parts of polyimide composite fiber, 10-15 parts of epoxidized polybutadiene, 3-5 parts of silane coupling agent, and 5-10 parts of diluent;
[0008] The polyimide composite fiber is prepared by a method comprising the following steps: 1) immersing nanoparticles in an alcoholysis solution of an aminosilane coupling agent for amino functionalization to obtain amino-modified nanoparticles; the nanoparticles are selected from at least one of nano-hydrotalcite, nano-hydroxyapatite, and nano-zeolite; 2) treating the polyimide fiber with nitric acid to obtain functionalized fiber; and 3) dispersing the amino-modified nanoparticles in an aprotic organic solvent to obtain a dispersion, immersing the functionalized fiber in the dispersion, and reacting to obtain the polyimide composite fiber.
[0009] In step 1), the average particle size of the nanoparticles is 50-100 nm, and the aminosilane coupling agent is selected from one or a combination of two or more of p-aminophenyltrimethoxysilane, p-aminophenyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane. The concentration of the aminosilane coupling agent in the alcoholysis solution is 1-2 wt%.
[0010] Furthermore, in step 1), the alcoholysis solution of the aminosilane coupling agent is a mixture of a C1-3 alcohol and water in a mass ratio of 90-95:5-10, the pH of which is adjusted to 4.5-5.5, the aminosilane coupling agent is added, and the mixture is allowed to stand for 5-10 minutes; the concentration of the aminosilane coupling agent in the alcoholysis solution is 1-5 wt%. The amino-functionalization of the nanoparticles is performed by adding the nanoparticles to the alcoholysis solution of the aminosilane coupling agent, ultrasonically dispersing the nanoparticles, and performing a modification reaction under stirring to obtain the nanoparticles.
[0011] Furthermore, the mass ratio of the aminosilane coupling agent to the nanoparticles is 5-8:100. The ultrasonic dispersion is performed at a power of 200-300 W and a frequency of 50-80 kHz for 10-30 minutes. The stirring speed is 500-800 rpm. The modification reaction is performed at 40-60°C for 0.5-1 hour. After completion of the reaction, centrifugation, washing, and drying are sequentially performed. The washing step is performed with water 1-3 times. The drying step is performed at 100-120°C for 5-15 minutes.
[0012] In step 2), the mass volume ratio of the polyimide fiber to the nitric acid solution is 1 g:7-10 mL, the concentration of the nitric acid solution is 65-68 wt %, and the soaking time is 1-3 hours.
[0013] Furthermore, the polyimide fiber has a specification of (1-3)D×(3-6)mm. The nitric acid treatment of the polyimide fiber comprises: soaking the polyimide fiber in a nitric acid solution, removing it, washing it, and drying it. The drying step comprises drying it at 60-100°C to a constant weight.
[0014] In step 3), the concentration of amino-modified particles in the dispersion is 1-3 wt %, the mass-to-volume ratio of the functionalized fiber to the dispersion is 1 g:5-8 mL, and the immersion time is 3-5 min.
[0015] Furthermore, after the dipping, the process includes taking out and drying the mixture, wherein the drying step is performed at a temperature of 90-120° C. for 2-4 hours.
[0016] Furthermore, the aprotic organic solvent is selected from one or a combination of two or more of acetone, ether, tetrahydrofuran, ethyl acetate, and ethyl butyrate. The dispersion is performed at a power of 200-300 W and a frequency of 50-80 kHz for 10-30 minutes.
[0017] The epoxidized polybutadiene has a number average molecular weight of 3000-5500, and the epoxy segment accounts for 40-50 wt%.
[0018] Polyimide fibers grafted with nanoparticles on their surfaces are exploited for their chloride ion adsorption properties and for forming a complex mechanical interlocking structure with resin and glass fiber cloth to improve resistance to chloride freeze-thaw cycles. However, polyimide composite fibers inherently possess high strength and modulus, resulting in significant rigidity. Their use can increase the brittle fracture of the entire fiberglass reinforced plastic composite material when subjected to external forces, reducing its impact strength. The inventors have discovered that epoxidized polybutadiene can improve impact toughness without compromising flexural strength. However, the amount of epoxidized polybutadiene relative to the polyimide composite fiber must be carefully controlled: too much can reduce flexural strength, while too little can significantly alter toughness.
[0019] The epoxy resin is a bisphenol A type epoxy resin with an epoxy value of 0.44-0.51.
[0020] The curing agent is an aromatic amine curing agent, selected from one or a combination of two or more of m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone, m-xylene diamine, m-aminobenzylamine, benzidine, and 2,6-diaminopyridine.
[0021] The silane coupling agent is selected from one or a combination of aminosilane coupling agents and epoxysilane coupling agents.
[0022] The diluent is selected from one or a combination of two or more of n-butyl glycidyl ether, allyl glycidyl ether, 5-ethylhexyl glycidyl ether, styrene oxide, and phenyl glycidyl ether.
[0023] The gram weight of glass fiber cloth is 300-600g / m 2 , width is 0.5-1m, thickness is 0.2-0.5mm.
[0024] The present invention also provides a method for preparing the chloride salt freeze-thaw resistant glass fiber reinforced plastic composite material, comprising the following steps:
[0025] The epoxy resin, curing agent, polyimide composite fiber, epoxidized polybutadiene, silane coupling agent and diluent are uniformly mixed to obtain glue solution, the alkali-free glass fiber cloth is immersed in the obtained glue solution, and then it is wound by a winding machine, cured and demolded to obtain the chloride salt freeze-thaw resistant glass fiber reinforced plastic composite material.
[0026] The curing temperature is 20-40° C., and the curing time is 1-7 days.
[0027] The application of the above-mentioned chloride-salt freeze-thaw-resistant fiberglass reinforced plastic composite material provided by the present invention in the preparation of a box-type water intake head has the advantages of being light, high-strength, and chloride-salt freeze-thaw-resistant. In particular, it can better resist the influence of freeze-thaw cycles in salt water environments, maintain structural integrity and stability, and can be applied to more severe natural water environments.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The chloride-freeze-thaw-resistant glass fiber reinforced plastic composite material provided by the present invention includes a polyimide fiber with nanoparticles grafted onto its surface via chemical bonds. The grafted nanoparticles not only have good adsorption properties for chloride ions, but also increase the roughness of the polyimide fiber surface, forming a complex mechanical interlocking structure with the resin and the glass fiber cloth, thereby enhancing the physical meshing effect between the resin and the glass fiber cloth interface, increasing the interface strength, and improving the chloride-freeze-thaw cycle resistance. The composite material is suitable for use as a water intake head material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a structural diagram of a series box-type water intake head in an application example;
[0031] Figure 2 Schematic diagram of the cross section of the water intake head at the sedimentation promotion part.
[0032] In the attached figure: 1-water intake head, 2-connecting pipe, 3-water intake pipe, 4-water inlet, 5-counterweight interlayer, 6-sedimentation promoting part, 7-submersible sewage pump, 8-top plate, 9-manhole, 10-hoist, 11-water baffle, 12-partition bottom plate, 13-sand discharge pipe, 14-sand leakage port, 15-rotating motor, 23-support column, 24-sealing ring sleeve. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with specific embodiment, but is not limited to the content on the specification sheets. Unless otherwise specified, "parts" described in the embodiments of the present invention are all parts by weight. All reagents used are commercially available reagents in this area.
[0034] The average particle size of nano-hydrotalcite was 50 nm and it was purchased from Taian Shenhao Chemical Co., Ltd.
[0035] The polyimide fiber had a specification of 1.0D×6 mm and was purchased from Jiangsu Xiannuo New Material Technology Co., Ltd.
[0036] EWR500-100 alkali-free glass fiber cloth, weight 480g / m 2 , 1m wide and 0.5mm thick, purchased from Wuhan Jiyesheng Chemical Co., Ltd.
[0037] Epoxidized polybutadiene PB4700, with a number average molecular weight of 3100 and an epoxy segment accounting for 50 wt%, was purchased from Daicel Corporation of Japan.
[0038] Epoxidized polybutadiene PB3600, with a number average molecular weight of 5400 and an epoxy segment ratio of 42 wt%, was purchased from Daicel Corporation of Japan.
[0039] Example 1
[0040] 1) Ethanol and water were mixed at a mass ratio of 90:10, and the pH was adjusted to 4.5 to obtain an alcohol / water solution. 3-Aminopropyltrimethoxysilane was added to the alcohol / water solution, mixed, and allowed to stand for 10 minutes to obtain an alcoholysis solution with a concentration of 2 wt%. 8 g of nano-hydrotalcite was added to 100 g of the alcoholysis solution and ultrasonically dispersed at a power of 200 W and a frequency of 50 kHz for 30 minutes. The modified particles were then subjected to a modification reaction at a stirring speed of 800 r / min and 40°C for 0.5 hours. After the reaction, the particles were centrifuged, washed with water three times, and dried at 100°C for 15 minutes to obtain amino-modified particles.
[0041] 2) Soak the polyimide fiber in a 65 wt% nitric acid solution at a mass volume ratio of 1 g:10 mL for 1 hour, remove it, rinse it with water three times, and dry it at 60°C to constant weight to obtain a functionalized fiber;
[0042] 3) The amino-modified particles were ultrasonically dispersed in acetone at a power of 300 W and a frequency of 50 kHz for 30 min to obtain a dispersion with an amino-modified particle concentration of 3 wt%. The functionalized fiber was immersed in the dispersion at a mass volume ratio of 1 g:8 mL for 5 min, removed, and dried at 120°C for 4 h to obtain the nanoparticle-modified polyimide fiber.
[0043] 4) 100 parts by mass of epoxy resin E51, 30 parts by mass of diaminodiphenylmethane, 40 parts by mass of polyimide composite fiber, 15 parts by mass of epoxidized polybutadiene PB4700, 5 parts by mass of 3-(2,3-glycidoxypropyl)trimethoxysilane, and 10 parts by mass of n-butyl glycidyl ether were mixed uniformly to obtain a glue solution, 500 parts by mass of alkali-free glass fiber cloth were soaked in the obtained glue solution, and then the alkali-free glass fiber cloth was passed through the core shaft of the winding machine and wound from the head to the tail of a cylindrical mold with a diameter of 1.5 meters and a height of 2 meters with a pitch of 1.022m and a circumferential winding angle of 78°, and then from the tail to the head, for 13 turns. The winding was stopped, the cloth was cut, and the cloth was cured at 20°C for 7 days. The cloth was demolded to obtain a chloride salt freeze-thaw resistant glass fiber reinforced plastic composite material with a wall thickness of 3 mm.
[0044] Example 2
[0045] The rest is the same as Example 1, except that in step 4), the amount of polyimide composite fiber used is 30 parts by mass.
[0046] Example 3
[0047] The rest is the same as Example 1, except that in step 4), an equal mass of epoxidized polybutadiene PB3600 is used instead of epoxidized polybutadiene PB4700.
[0048] Example 4
[0049] The rest is the same as Example 1, except that in step 4), the amount of epoxidized polybutadiene PB4700 used is 10 parts by mass.
[0050] Example 5
[0051] The rest is the same as Example 1, except that in step 3), the functionalized fiber is immersed in the dispersion at a mass volume ratio of 1 g:5 mL for 5 min.
[0052] Example 6
[0053] 1) Ethanol and water were mixed at a mass ratio of 90:10, and the pH was adjusted to 4.5 to obtain an alcohol / water solution. 3-Aminopropyltrimethoxysilane was added to the alcohol / water solution, mixed, and allowed to stand for 5-10 minutes to obtain an alcoholysis solution with a concentration of 2 wt%. 5 g of nano-hydrotalcite was added to 100 g of the alcoholysis solution and ultrasonically dispersed at a power of 200 W and a frequency of 50 kHz for 30 minutes. The modified particles were then stirred at a speed of 800 r / min and at 40°C for 0.5 hours. After the reaction, the particles were centrifuged, washed with water three times, and dried at 100°C for 15 minutes to obtain amino-modified particles.
[0054] 2) Immerse the polyimide fiber in a 68 wt% nitric acid solution at a mass volume ratio of 1 g:7 mL for 3 h, remove it, rinse it with water three times, and dry it at 60°C to constant weight to obtain a functionalized fiber;
[0055] 3) The amino-modified particles were ultrasonically dispersed in acetone at a power of 300 W and a frequency of 50 kHz for 30 min to obtain a dispersion with an amino-modified particle concentration of 3 wt%. The functionalized fiber was immersed in the dispersion at a mass volume ratio of 1 g:8 mL for 5 min, removed, and dried at 90°C for 4 h to obtain the nanoparticle-modified polyimide fiber.
[0056] 4) 100 parts by mass of epoxy resin E44, 30 parts by mass of diaminodiphenylmethane, 40 parts by mass of polyimide composite fiber, 15 parts by mass of epoxidized polybutadiene PB4700, 5 parts by mass of 3-(2,3-epoxypropyl)trimethoxysilane, and 5 parts by mass of n-butyl glycidyl ether were mixed evenly to obtain a glue solution, 400 parts by mass of alkali-free glass fiber cloth were soaked in the obtained glue solution, and then the alkali-free glass fiber cloth was passed through the core shaft of the winding machine and wound from the head to the tail of a cylindrical mold with a radius of 2.5 m and a height of 10 m with a pitch of 0.7 m and a winding angle of 4°, and then from the tail to the head. This was repeated 30 times, and the winding was stopped, cut, cured at 20°C for 7 days, and demolded to obtain a chloride salt freeze-thaw resistant glass fiber reinforced plastic composite material.
[0057] Comparative Example 1
[0058] The rest is the same as Example 1, except that there is no step 1) to 3), that is, no nano-hydrotalcite modified polyimide fiber
[0059] 100 parts by mass of epoxy resin E51, 30 parts by mass of diaminodiphenylmethane, 40 parts by mass of polyimide fiber, 15 parts by mass of epoxidized polybutadiene PB4700, 5 parts by mass of 3-(2,3-epoxypropoxypropyl)trimethoxysilane, and 10 parts by mass of n-butyl glycidyl ether were mixed uniformly to obtain a glue solution, 500 parts by mass of alkali-free glass fiber cloth were immersed in the obtained glue solution, and then the alkali-free glass fiber cloth was passed through the core shaft of a winding machine and wound from the head to the tail of a cylindrical mold with a radius of 2.5 m and a height of 10 m with a pitch of 0.7 m and a winding angle of 4°, and then wound from the tail to the head, for 13 turns, and then the winding was stopped, cut, cured at 20°C for 7 days, and demolded to obtain a chloride salt freeze-thaw resistant glass fiber reinforced plastic composite material.
[0060] Comparative Example 2
[0061] The rest is the same as Example 1, except that in step 4),
[0062] 100 parts by mass of epoxy resin E51, 30 parts by mass of diaminodiphenylmethane, 4 parts by mass of nano-hydrotalcite, 15 parts by mass of epoxidized polybutadiene PB4700, 5 parts by mass of 3-(2,3-epoxypropoxypropyl)trimethoxysilane, and 10 parts by mass of n-butyl glycidyl ether were mixed to obtain a glue solution, 500 parts by mass of alkali-free glass fiber cloth were immersed in the obtained glue solution, and then the alkali-free glass fiber cloth was passed through the core shaft of a winding machine and wound from the head to the tail of a cylindrical mold with a radius of 2.5 m and a height of 10 m, and then from the tail to the head, for 13 turns, and then the winding was stopped, cut, cured at 20°C for 7 days, and demolded to obtain a chloride salt freeze-thaw resistant glass fiber reinforced plastic composite material.
[0063] Comparative Example 3
[0064] The rest is the same as Example 1, except that in step 4), the amount of epoxidized polybutadiene PB4700 used is 5 parts by mass.
[0065] Comparative Example 4
[0066] The rest is the same as Example 1, except that in step 4), the amount of epoxidized polybutadiene PB4700 used is 20 parts by mass.
[0067] Application Example 1
[0068] The series box-type water intake head includes two water intake heads 1, which are interconnected through a connecting pipe 2 and then connected to a water intake pipe 3; the water intake head is cylindrical and made of the chloride-freeze-thaw-resistant fiberglass composite material of Example 1. A water inlet 4 is provided on the upper part of the water intake head, and a grid is provided at the water inlet 4; a counterweight interlayer 5 is provided on the lower part of the outer side of the water intake head 1 for accommodating a counterweight to stabilize the water intake head 1.
[0069] A sedimentation-promoting portion 6 protruding upward is provided in the middle of the bottom of the water intake head 1. The sedimentation-promoting portion 6 has inclined side surfaces, which help the sediment in the water intake head to slide and settle along the side surfaces of the sedimentation-promoting portion 6. The interior of the sedimentation-promoting portion 6 is hollow and is provided with a submersible sewage pump 7. The submersible sewage pump 7 is used to discharge the sediment at the bottom of the water intake head to the outside of the water intake head to replenish the sediment lost after the original mud surface is lowered due to scouring, thereby improving the stability of the water intake head.
[0070] The water intake head 1 is cylindrical, with a top plate 8 on the top, and an openable and closable inspection hole 9 on the top plate 8; a hoist 10 is provided above the top plate 8, which is used to connect and control the water baffles 11 of the two circles of water inlets 4 respectively, so as to control the water intake of each water inlet 4.
[0071] Support columns 23 are provided on the inner wall or outer wall of the vertical side wall of the water intake head. The support columns are evenly distributed along the circumference of the water intake head to improve the strength and stability of the water intake head.
[0072] The connecting pipe 2 needs to be connected in sections, and a sealing ring sleeve 24 is sleeved on the outside of the joint for sealing the connection.
[0073] A cavity is provided at the bottom of the water intake head. A partition bottom plate 12 is provided between the cavity and the water storage space inside the water intake head to prevent water from entering the cavity. The bottom of the sedimentation promoting part 6 is provided on the partition bottom plate 12 .
[0074] A sand discharge pipe 13 is provided inside the cavity. One end of the sand discharge pipe 13 passes through the partition bottom plate 12 and is connected to the outlet of the submersible sewage pump 7, and the other end passes through the bottom side wall of the water intake head and is above the initial mud surface. The mud and sand deposited at the bottom of the water intake head are discharged to the outside of the water intake head through the submersible sewage pump 7 and the sand discharge pipe 13.
[0075] The sedimentation promoting portion 6 is conical or truncated cone-shaped, and is small at the top and large at the bottom. The inclined side wall of the sedimentation promoting portion 6 and the inner wall of the water intake head form a circle of sedimentation space that is large at the top and small at the bottom. The bottom of the sedimentation space is a partition bottom plate 12, and a number of sand leakage ports 14 are evenly arranged. The sand leakage ports 14 are connected to the inlet of the submersible sewage pump 7 through a pipe.
[0076] The sedimentation promoting portion 6 and the partition bottom plate 12 below form a closed space, in which a submersible sewage pump 7 and a rotating motor 15 are arranged.
[0077] The composite materials prepared in the above examples and comparative examples were subjected to the following performance tests:
[0078] Impact resistance: With reference to the standard GB / T1451-2005 fiber reinforced plastic simply supported beam impact toughness test method, the impact resistance reflects the ability of the water head to resist damage under impact load.
[0079] Bending strength: Tested in accordance with GB / T 1449-2005, Test Method for Bending Properties of Fiber-Reinforced Plastics. Bending strength reflects the deformation resistance and load-bearing performance of the water intake head under bending load.
[0080] Resistance to chloride freeze-thaw cycles: Referring to standard GB / T 50082-2009, the test medium is artificial seawater prepared with 3.5wt% sodium chloride and deionized water. Quick freezing method: (-15±2)℃ / 2h, (8±2)℃ / 2h, cycle 1000 times, retest the impact strength and longitudinal bending strength, and calculate the strength loss rate.
[0081] Table 1 Performance test results
[0082] .
[0083] As can be seen from Table 1, the composite material prepared by the present invention has good chloride salt freeze-thaw cycle resistance and mechanical properties.
[0084] The above detailed description is a specific description of one feasible embodiment of the present invention. This embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not depart from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A glass fiber reinforced plastic composite material resistant to chloride salt freeze-thaw cycles, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20-30 parts of curing agent, 400-500 parts of alkali-free glass fiber cloth, 30-40 parts of polyimide composite fiber, 10-15 parts of epoxidized polybutadiene, 3-5 parts of silane coupling agent, and 5-10 parts of diluent; The polyimide composite fiber is prepared by a method comprising the following steps: 1) immersing nanoparticles in an alcoholysis solution of an aminosilane coupling agent for amino functionalization to obtain amino-modified nanoparticles; the nanoparticles are selected from at least one of nano-hydrotalcite, nano-hydroxyapatite, and nano-zeolite; 2) treating the polyimide fiber with nitric acid to obtain functionalized fiber; 3) dispersing the amino-modified nanoparticles in an aprotic organic solvent to obtain a dispersion, immersing the functionalized fiber in the dispersion, and reacting to obtain the polyimide composite fiber. In step 2), the polyimide fiber is subjected to nitric acid treatment by soaking the polyimide fiber in a nitric acid solution, taking it out, washing it, and drying it; the polyimide fiber has a specification of (1-3)D×(3-6)mm; the mass volume ratio of the polyimide fiber to the nitric acid solution is 1g:7-10mL; the concentration of the nitric acid solution is 65-68wt%; the soaking time is 1-3h; and the drying is performed at 60-100°C to a constant weight; The alkali-free glass fiber cloth has a gram weight of 300-600 g / m 2 , width is 0.5-1m, thickness is 0.2-0.5mm.
2. The chloride salt freeze-thaw cycle resistant glass fiber reinforced plastic composite material according to claim 1, characterized in that: In step 1), the average particle size of the nanoparticles is 50-100 nm; the aminosilane coupling agent is selected from one or a combination of two or more of p-aminophenyltrimethoxysilane, p-aminophenyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; the concentration of the aminosilane coupling agent in the alcoholysis solution of the aminosilane coupling agent is 1-5wt%; and the mass ratio of the aminosilane coupling agent to the nanoparticles is 5-8:
100.
3. The chloride salt freeze-thaw cycle resistant glass fiber reinforced plastic composite material according to claim 1, characterized in that: In step 3), the concentration of amino-modified particles in the dispersion is 1-3 wt %; the mass volume ratio of the functionalized fiber to the dispersion is 1 g:5-8 mL; and the immersion time is 3-5 min.
4. The chloride salt freeze-thaw cycle resistant glass fiber reinforced plastic composite material according to claim 1, characterized in that: The epoxidized polybutadiene has a number average molecular weight of 3000-5500, and the epoxy segment accounts for 40-50 wt%.
5. The chloride salt freeze-thaw cycle resistant glass fiber reinforced plastic composite material according to claim 1, characterized in that: The epoxy resin is a bisphenol A epoxy resin with an epoxy value of 0.44-0.51; the curing agent is an aromatic amine curing agent, selected from one or a combination of two or more of m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone, m-xylenediamine, m-aminobenzylamine, benzidine, and 2,6-diaminopyridine; the silane coupling agent is selected from one or a combination of two of aminosilane coupling agents and epoxysilane coupling agents; the diluent is selected from one or a combination of two or more of n-butyl glycidyl ether, allyl glycidyl ether, 5-ethylhexyl glycidyl ether, styrene oxide, and phenyl glycidyl ether.
6. The method for preparing the chloride salt freeze-thaw cycle resistant glass fiber reinforced plastic composite material according to any one of claims 1 to 5, characterized in that: The steps include: Epoxy resin, curing agent, polyimide composite fiber, epoxidized polybutadiene, silane coupling agent and diluent are uniformly mixed to obtain glue solution, alkali-free glass fiber cloth is immersed in the obtained glue solution, and then wound by a winding machine, cured and demolded to obtain chloride salt freeze-thaw cycle resistant glass fiber reinforced plastic composite material.
7. Use of the chloride salt freeze-thaw cycle resistant fiberglass reinforced plastic composite material according to any one of claims 1 to 5 in the preparation of a box-type water intake head.
Citation Information
Patent Citations
Multifunctional sea water taking head part
CN103556673B
High-pressure epoxy fiberglass pipes and their preparation method with added glass fiber fabric
CN105175998B
Glass fiber reinforced plastic prepreg for high-speed fan blade
CN113897029A